(untitled) (Global Journal of Human-Social Science, 2025)
The Rana Plaza collapse in Dhaka, Bangladesh, on April 24, 2013, marked one of the deadliest industrial disasters in modern history, claiming over 1,100 lives and injuring more than 2,500 workers. This paper critically assesses the role of the Rana Plaza Coordination Cell (RPCC), established by the Ministry of Labour and Employment, in addressing the multifaceted challenges of disaster rehabilitation. Utilizing a qualitative methodology including focus group discussions, key informant interviews, and analysis of secondary documents, this research examines how the RPCC navigated issues of coordination, data verification, emergency relief, and compensation. Findings reveal that despite initial fragmentation, the RPCC played a central role in mitigating information gaps and facilitating victim support through institutional innovations and stakeholder collaboration. The paper recommends institutionalizing such coordination mechanisms for future industrial disasters to ensure timely, equitable, and efficient rehabilitation outcomes.